1962
DOI: 10.1063/1.1777179
|View full text |Cite
|
Sign up to set email alerts
|

A Photometric Procedure for Weight Determination of Submicroscopic Particles Quantitative Electron Microscopy

Abstract: A photometric procedure for rapid determination of weight of isolated particles down to a size of 200 A is described. Under normal conditions of electron microscopy, weights of down to 10−18 g can be determined with an inaccuracy of less than 10%. By lowering the accuracy or using more elaborate measures (such as very low accelerating voltage) one to two orders of magnitude for the lower weight limit can be gained. The method can now be applied to population studies of biologic particles, especially those of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
2

Year Published

1967
1967
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(44 citation statements)
references
References 5 publications
1
41
0
2
Order By: Relevance
“…12,13 Consequently, it can be shown that the effective ͑average͒ optical potential of an optical lattice, i , for the voxel around the point ͑x , y͒ is…”
mentioning
confidence: 99%
“…12,13 Consequently, it can be shown that the effective ͑average͒ optical potential of an optical lattice, i , for the voxel around the point ͑x , y͒ is…”
mentioning
confidence: 99%
“…Cantilever-based techniques have recently been demonstrated for mass detection at the zeptogram level (10 À21 g) [8,9]. Electronmicroscopy-based techniques have a long history [6,7,[10][11][12][13][14][15][16][17][18]. In Zeitler and Bahr's early work of 1962, the mass of nanoparticles has been determined down to 10 À18 g using STEM with an accuracy of 10% [17].…”
mentioning
confidence: 99%
“…There was no measurable contamination of specimens exposed to normal beam currents for up to 30 min. Electrography was at carefully controlled magnifications and controlled background exposure (14,15). Plates were processed according to a standard technique.…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, the chromosomes appear in natural contrast since no special fixatives or heavy-metal stains are required for their visualization. By means of certain operating conditions of the electron microscope, controlled exposure, and controlled photographic processing, a close proportionality of the dry mass of the object to photometric transmission in the electrographic negative can be achieved (14,15). Since the relationship of mass and contrast (difference of transmission T -Tot) is independent of the object's shape and its chemical composition, the electron microscope constitutes a sensitive balance.…”
mentioning
confidence: 99%